A Commemorative Issue in Honor of Professor Nick Hadjiliadis: Metal Complex Interactions with Nucleic Acids and/or DNA - Christina N. Banti (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Special Issue of the International Journal of Molecular Science comprises a comprehensive study on "Metal Complex Interactions with Nucleic Acids and/or DNA". This Special Issue has been inspired by the important contribution of Prof. Nick Hadjiliadis to the field of palladium or/and platinum/nucleic acid interactions. It covers a selection of recent research and review articles in the field of metal complex interactions with nucleic acids and/or DNA. Moreover, this Special Issue on "Metal Complexes Interactions with Nucleic Acids and/or DNA" provides an overview of this increasingly diverse field, presenting recent developments and the latest research with particular emphasis on metal-based drugs and metal ion toxicity.